Comparative study of colour usage on classroom wall: a case study of SMK Tendong Pasir Mas, Kelantan / Amira Halyani Abdullah Habib, Mohd Zikri Mohd Zaki, Mayamin Yuhaniz .. [et al.] - Abdullah Habib, Amira Halyani; Mohd Zaki, Mohd Zikri; Yuhaniz, Mayamin (2023)
Colour schemes are crucial in assessing educational environments as they impact the teaching and learning process, as well as students’ behaviour and attitudes. Inappropriate or unsuitable use of colour can diminish students’ enthusiasm and reduce their focus in classroom. The aim of this research is to investigate the impact of wall colours in classrooms on the mood and behaviour of students. The study focuses on three secondary school classrooms at SMK Tendong Pasir Mas, Kelantan where each painted in a different colour which are blue, orange, and white. A total of 71 students were given questionnaires and the classroom painted with blue colour (cool colour) is the most preferred by students which is found to promote focus and induce a sense of calmness and followed by white which was discovered to evoke a feeling of relaxation. In contrast, orange, the least preferred colour stimulates excitement but may disrupt sense of calmness and diminish freshness. For future research, it is recommended to involve broader range of schools as participants and enable more comprehensive analysis of how different types of educational institution perceive and evaluate the impact of colour usage on classroom walls. Understanding of colour will enable designer to make informed decisions when choosing appropriate colour for educational environments, aligning them with their intended purposes.